Inclusive pedagogical narratives in vulnerable educational contexts: the student’s voice (2019)
The current article is the result of a macro research project called “Inclusive pedagogical narratives in vulnerable educational contexts. Case: Institución Educativa Compartir las Brisas” registered in the research directorate of the Catholic University of Pereira – DII-012-003. It is established in an intermediate phase report which wants to configure the basis, the purpose of the project and the preliminary progress. It was done the characterization of the context through the social cartography, identifying the principal risk and protective factors latent in the community. In the design were used as data collection tools as well as the social cartography, real life stories, photography’s workshops and psychosocial sessions. The photography and accounts were the children’s voices who gave way to the theoretical reflection of themselves, in the data analysis process was used the encoding and decoding categories process, according to Marquínez (2013) let develop concepts and within analyze the accounts from the photography.